Ars Vivendi and Therapeutics in Nietzsche: Some Contributions for a Philosophy of Medicine; [Ars Vivendi y Terapéutica en Nietzsche: Algunos Aportes Para Una Filosofía de la Medicina] - Aurenque-Stephan, D (Universidad Compultense Madrid, 2023)
Friedrich Nietzsche has become one of the most influential and well-known exponents of philosophy. However while many of its fundamental concepts are increasingly understood and discussed, the Spanish-speaking world knows less about its therapeutic philosophy. Thus, this article aims to contribute to enriching the list of works that have allowed Nietzsche to be rediscovered not only as a philosopher of ars vivendi, but very particularly as a philosopher of medicine. Specially, I will try to interpret some of the most fruitful approaches in his thinking for contemporary debates in the philosophy of medicine. © 2023 Universidad Complutense de Madrid. All rights reserved.